Modular Chaos for Random Processes - Akhmet, Marat (Discontinuity, Nonlinearity, and Complexity, 2026)
We apply the method of domain structured chaos for a dynamics with orbits whirling among infinitely many modules. Thus, the conservative conditions of chaos existence are weakened to model irregular dynamics. The research proves that the Poincar\’e chaos is of exceptional use for analysis of stochastic processes. Examples, illustrating the results are provided.